Civil Liability for the Establishment of a Micro, Small, and Medium-sized enterprise sole proprietorship - Rezha Awaladi Ramadha Fath (Universitas Islam Malang, 2022)
The author discussing legal liability in the civil sector for the establishment of a sole proprietorship as one of the branches of a limited company which has begun to be established by individuals as a result of the birth and enactment of the Job Creation Act. Where the purpose of the research is to identify and provide an explanation regarding to the problem of the legal status of sole proprietorship if it is explored about the fulfillment of the elements in limited company as a legal entity in order to see the legal consequences of civil liability imposed on the establishment of an individual limited liability company in terms of articles 1365, 1366 and 1367 of Â Burgerlijk Wetbook. This research is a normative research using statutory approach and historical approach. The conclusions of this study are: first, the regulation of a sole proprietorship according to the research conducted by the author couldnâ€™t called as limited company because it does not meet the initial philosophy of the limited company, namely sero which means the sharing of shares that form into a single entity so as to make the company, apart from Apart from that, the exception that excludes the provisions in a limited liability company against the establishment of an individual is in fact also contrary to the prerequisites for a business to be referred to as an UMKM. So seeing this situation, it might be better if a sole proprietorship is not referred to as a limited company but rather an individual company. Second, the regulation regarding the civil liability of a private company is the same as the form of liability carried out by an individual company where the form of liability is the responsibility carried out by the directors individually and can also be carried out jointly and severally. Meanwhile, the Company's shareholders are not personally responsible for the engagements made on behalf of the Company and are not responsible for the Company's losses in excess of the shares owned. The provisions in this article emphasize the characteristics of the Company that shareholders are only responsible for the amount of the deposit for all shares and do not include their personal assets.